Coastal Tourism Destinations in West Bengal: Historical Background and Development - Baitalik, Anirban; Majumdar, Sankar (International Journal of Social Sciences and Management, 2015)
Coastal tourism has become a major facet of modern life. Further, tourism development in the coastal zone has become a constant since the end of World War II. Coastal tourism is a process involving tourists and the people and places they visit, particularly the coastal environment and its natural and cultural resources. Most coastal tourism takes place along the shore and in the water immediately adjacent to the shoreline. In India Goa, Kerala, Karnataka were emerged spontaneously as a coastal tourism destination in the 1960s, its unique selling points being its natural coastal beauty. But the history of coastal tourism is not very old in West Bengal. The coastal stretch of West Bengal with a length of about 350 kilometer comprises the two districts- Purba Medinipur and Dakshin Chabbisparagana. In West Bengal there are many popular coastal tourism destinations, but coastal tourism in West Bengal started in 1980s. Present study focuses on historical background and development of the coastal tourism destinations in West Bengal. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 267-272 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12910